1988
DOI: 10.1111/j.1749-6632.1988.tb38504.x
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Glass‐Ceramics in Middle Ear Surgery An 8‐Year Reviewa

Abstract: An 8-year follow-up of Ceravital middle ear prostheses showed there was extremely good tolerance in the middle ear space. Incompatibility phenomena were not observed, and inflammatory reactions were neither caused nor supported by the implants. The tympanoplasties were always performed without interposition of cartilage between the tympanic membrane or the tympanic membrane graft and the disk-shaped portion of the implant, and extrusions were never observed. Long-lasting inflammatory processes appeared to dest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 4 publications
1
27
0
2
Order By: Relevance
“…The use of Biog1ass® 45 S5 implants in midd1e ear surgery to rep1ace ossic1es damaged by chronic infection is also successfu1, and results are encouraging ( Reck et al, 1988;Merwin, 1990;Wilson et al , 1995). Biog1ass® midd1e ear implants are shown in Fig.…”
Section: 5 Clinical Applicationsmentioning
confidence: 96%
“…The use of Biog1ass® 45 S5 implants in midd1e ear surgery to rep1ace ossic1es damaged by chronic infection is also successfu1, and results are encouraging ( Reck et al, 1988;Merwin, 1990;Wilson et al , 1995). Biog1ass® midd1e ear implants are shown in Fig.…”
Section: 5 Clinical Applicationsmentioning
confidence: 96%
“…Animal experiments with Ceravital showed better middle ear compatibility compared to polymers [18], and initial clinical results were favorable [19]. After 5 years of implantation, the extrusion rate was still less than 10% [20] but, in inflamed ears, biodegradation destroyed the necessary mechanical stability [21].…”
Section: Discussionmentioning
confidence: 99%
“…After eight years of clinical use of Ceravital ® , Reck et al (87) concluded that this material provides the most effective prostheses for complete reconstruction of the ossicular chain.…”
Section: Clinical Uses Of Bioactive Glasses and Glass-ceramicsmentioning
confidence: 99%